2022
DOI: 10.52547/jrums.21.5.551
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the prevalence and Causes of Suicide (Thoughts and Actions) In Iranian School and University Students

Abstract: Background and Objectives: Suicide is a serious issue, so it needs to be addressed. The purpose of this review study is to a Systematic Review on the prevalence and Causes of Suicide (Thoughts and Actions) In Iranian School and University Students. Materials and Methods:This study is a systematic review carried out in April 2022, using different search engines including SID, Magiran, Google Scholar, Sciencedirect, PubMed, Scopus, as well as the keywords "Suicide", "University", "Student", and their Persian equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Between 2012 and 2016, a total of 1159 suicide cases were reported, and among the 27 cities in the province, Izeh had the highest suicide rate during these five years, with 75 suicides per population ratio (21). Moreover, studies conducted on the prevalence of suicidal thoughts among Iranian students have reported a rate of up to 7.49% (22). The student population constitutes a considerable portion of the country's young generation and will be the future builders of the nation.…”
mentioning
confidence: 99%
“…Between 2012 and 2016, a total of 1159 suicide cases were reported, and among the 27 cities in the province, Izeh had the highest suicide rate during these five years, with 75 suicides per population ratio (21). Moreover, studies conducted on the prevalence of suicidal thoughts among Iranian students have reported a rate of up to 7.49% (22). The student population constitutes a considerable portion of the country's young generation and will be the future builders of the nation.…”
mentioning
confidence: 99%